Formação docente no Espírito Santo: Diálogos com a pesquisa "trabalho docente na educação básica no Brasil" - Oliveira, Dalva Ricas de (2014)
This dissertation aims to analyze the understandings of education professionals the final years of Elementary and Middle School of the state network of municipalities Guarapari, New Venecia, Viana and Victory, on the processes of initial and continuing training in the interface with the constitutive dimensions of identity and of the conditions of teachers' work, from the database of the Holy Spirit concerning the research "Teacher Work in Basic Education in Brazil", held in 2009, in seven States, included this, under the general coordination of the Study Group on Educational Policies and Work Professor, Federal University of Minas Gerais. The hypothesis under discussion is that the public policies educational deployed with the Holy Spirit in the last decades have promoted changes in constitutive dimensions of identity and of the conditions of teachers' work and also in the training of professionals in education, implying a low participation of these individuals in activities and programs of continuing education. It is a qualitative and quantitative study in which the methodology consists in the intercross data collected by survey said research, indicators of identity, profile and condition of teacher work with the indicators of training. The produced data held talks with the theoretical production of interlocutors Dubar, Nóvoa, Oliveira, Tardif, and Tardif, Lessard, in addition to the contribution from the authors included in the literature review. The results of this study indicate that the participation of the subjects of the sample in processes of continuing education was even less expressive than the one found in the Holy Spirit and in Brazil, and that the centrality acquired by the professor and their processes of initial and continuing training is not meant professional development and appropriate conditions of work taken as dimensions are inseparable and equally important for flamingos improvement in the quality of Basic Education, for example, by the predominance of low wages, despite the fact that the majority of participants be post-graduate, working in more than two educational units and the lack of support/guidance for working with students with special needs. These results meet the understandings of teachers since, although they have recognized their role as essential, not considered "receive more" "training for activity that exercises" between the three most important measures to improve the quality of the work.